Macroscopic and Microscopic Studies of Nanoparticles-Stabilized Foam for Carbon Dioxide Gas Flooding - ADNAN, NURNAJLA (2021)
The thesis presents microscopic and macroscopic studies of nanoparticlesstabilized foam stability for CO₂ gas flooding. CO₂ gas flooding experienced poor sweep efficiency due to high gas mobility, hence foam was utilized as the gas mobility control agent. However, previous research mostly restricted to foam stability at macroscale, while very few studies corroborated pore-scale studies with coreflood studies. This research aims to examine effects of nanoparticles concentration and varying salinity on foam static and dynamic stability at micro-scale and macro-scale. Foam static stability tests were conducted to determine the optimized surfactant-nanoparticles concentration via Design of Experiments (DOE). Microscopic and macroscopic foam studies were performed in micromodels and Bentheimer sandstone cores respectively. Optimized surfactant-nanoparticles concentration with the highest foam stability was 0.3 wt% for both Alpha Olefin Sulfonate (AOS) and silica nanoparticles (SiO₂). Results indicated AOS-SiO₂ foam generated thicker and more stable foam lamella that travelled through the pore network without rupturing to provide higher gas mobility control. AOS-SiO₂ foam flooding in high salinity environment shown significant increase in average pressure drop. This result implied SiO₂ nanoparticles worked synergistically with electrolyte mixtures to enhance the foam dynamic stability. Coreflood results validated optimized AOS-SiO₂ concentration was enough to enhance the foam stability without causing excessive aggregation and pore throat blockage. Overall, the microscopic and macroscopic studies justified the optimized AOS-SiO₂ foam has significantly improved the foam stability and gas mobility reduction, consequently having immense potential to enhance the overall macroscopic sweep efficiency.